Evaluation of ph stability, concentration and antimicrobial activity in commercial brands of sodium hypochlorite solution (Research, Society and Development, 2021)
The present work refers to an in vitro study of different commercial brands of sodium hypochlorite (manipulated, Soda Chlorine and Brilux) being evaluated by means of pH, antimicrobial action and concentration, at time intervals of 0, 7 and 14 days, in a refrigerated environment and at room temperature, and with receiving and absence of light. The antimicrobial assay of the solutions was performed by the disk diffusion method. Enterococcus faecalis was grown on Tryptic Soil Agar (TSA) (Merk) and incubated at ± 35ºC for 24 hours. The active chlorine content was verified by iodometric titration, and the pH, by pH measuring tape. The results suggest that there was no statistically significant relevance in the results of the active chlorine content. The pH became higher with time, and the antimicrobial activity was altered according to the storage location and time.